TEACHING TITRIMETRIC ANALYSIS THROUGH DIGITAL EDUCATIONAL TECHNOLOGIES: THE EXAMPLE OF THE CHEMCOLLECTIVE PROGRAM - M.D. Usmonova (Bright Mind Publishing, 2025)
This article analyzes the capabilities of the ChemCollective virtual laboratory in teaching one of the main branches of analytical chemistry titrimetric analysis (acid-base and redox titrations). The platform helps reinforce students’ theoretical knowledge, develop practical skills, and effectively conduct laboratory sessions even in remote learning environments.
Keywords: Analytical chemistry, titrimetric analysis, acid-base titration, redox titration, ChemCollective, virtual laboratory, digital education technologies, distance learning.